DNA Methylation Perturbations in Genes Involved in Polyunsaturated Fatty Acid Biosynthesis Associated with Depression and Suicide Risk - Haghighi, Fatemeh; Galfalvy, Hanga; Chen, Sean; Huang, Yung-yu; Cooper, Thomas B.; Burke, Ainsley K.; Oquendo, Maria A.; Mann, J. John; Sublette, M. Elizabeth (Frontiers in Neurology, 2015)
Polyunsaturated fatty acid (PUFA) status has been associated with neuropsychiatric disorders, including depression and risk of suicide. Long-chain PUFAs (LC-PUFAs) are obtained in the diet or produced by sequential desaturation and elongation of shorter-chain precursor fatty acids linoleic acid (LA, 18:2n-6) and α-linolenic acid (ALA, 18:3n-3). We compared DNA methylation patterns in genes involved in LC-PUFA biosynthesis in major depressive disorder (MDD) with (n=22) and without (n=39) history of suicide attempt, and age- and sex-matched healthy volunteers (n=59). Plasma levels of selected PUFAs along the LC-PUFA biosynthesis pathway were determined by transesterification and gas chromatography. CpG methylation levels for the main human LC-PUFA biosynthetic genes, fatty acid desaturases 1 (Fads1) and 2 (Fads2), and elongation of very long chain fatty acids protein 5 (Elovl5), were assayed by bisulfite pyrosequencing. Associations between PUFA levels and diagnosis or suicide attempt status did not survive correction for multiple testing. However, MDD diagnosis and suicide attempts were significantly associated with DNA methylation in Elovl5 gene regulatory regions. Also the relative roles of PUFA levels and DNA methylation with respect to diagnostic and suicide attempt status were determined by least absolute shrinkage and selection operator (LASSO) logistic regression analyses. We found that PUFA associations with suicide attempt status were explained by effects of Elovl5 DNA methylation within the regulatory regions. The observed link between plasma PUFA levels, DNA methylation, and suicide risk may have implications for modulation of disease-associated epigenetic marks by nutritional intervention.